Embryo transfer practices and multiple births resulting from assisted reproductive technology: an opportunity for prevention - Kissin, Dmitry M. (Fertil Steril, 2015)
OBJECTIVE: To evaluate assisted reproductive technology (ART) ET practices in the United States and assess the impact of these practices on multiple births, which pose health risks for both mothers and infants. DESIGN: Retrospective cohort analysis using the National ART Surveillance System data. SETTING: US fertility centers reporting to the National ART Surveillance System. PATIENT(S): Noncanceled ART cycles conducted in the United States in 2012. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Multiple birth (birth of two or more infants, at least one of whom was live-born). RESULT(S): Of 134,381 ART transfer cycles performed in 2012, 51,262 resulted in live births, of which 13,563 (26.5%) were multiple births: 13,123 twin and 440 triplet and higher order births. Almost half (46.1%) of these multiple births resulted from the following four cycle types: two fresh blastocyst transfers among favorable or average prognosis patients less than 35 years (1,931 and 1,341 multiple births, respectively), two fresh blastocyst transfers among donor-oocyte recipients (1,532 multiple births), and two frozen/thawed ETs among patients less than 35 years (1,452 multiple births). More than half of triplet or higher order births resulted from the transfer of two embryos (52.5% of births among fresh autologous transfers, 67.2% of births among donor-oocyte recipient transfers, and 42.9% among frozen/thawed autologous transfers). CONCLUSION(S): A substantial reduction of ART-related multiple (both twin and triplet or higher order) births in the United States could be achieved by single blastocyst transfers among favorable and average prognosis patients less than 35 years of age and donor-oocyte recipients.